Investigation on paint removal operation using multiple passes in waterjet cleaning process - Mohd Nazir, Mat Nawi (2021)
The need of cleaning automotive paint without secondary pollution has recently become a major concern globally. The waterjet technology has extended its application to include surface treatment, machining, cleaning and cutting of materials. Plain waterjet is frequently used for cleaning since its offers environmentally friendly concept which results near zero pollution to the surroundings. The present work aims to analyse and optimise the use of multiple passes in waterjet cleaning process for removal of automotive paint using response surface methodology (RSM) approach. The effect of surface roughness (Ra) and its topography were analysed. RSM, analysis of variance (ANOVA), fractional factorial at 2-levels and central composite design (CCD) were utilized to optimize the plain waterjet process parameters for effective cleaning of paint. It was observed that the lateral feed and pressure were the most significant control factors in influencing the cleaning performance criteria. Based on the surface topography, it was found that the paint was removed with varying degrees of substrate damage. A mathematical model was developed using linear regression analysis to predict the Ra in terms of cleaning parameters of plain waterjet process. The model had successfully predicted the Ra of the cleaned automotive parts within the limit of this study. A confirmation test at optimum parameters was later conducted to verify the improvement of quality characteristic during the waterjet paint removal process. The recommended optimal parametric combinations for better Ra were found to be waterjet pressure of 34 MPa, traverse rate of 500 mm/min, standoff distance of 10 mm, number of passes of 1 and lateral feed of 0.6 mm. It can be concluded that the selected optimal combination of plain waterjet parameters satisfies the actual requirement for cleaning of automotive paint in real practice. The results from the present work based on RSM and quantitative modelling are valuable in analysing the effect of various waterjet processing parameters thus attaining an appropriate control over the cleaning efficiency of automotive paint